Expression levels of key immune indicators and immune checkpoints in manganese-exposed rats - Yuanmeng Qi; Huifang Si; Xiaofei Jin; Yonghua Guo; Jiarui Xia; Jing He; Xuedan Deng; Meng Deng; Wu Yao; Changfu Hao (Ecotoxicology and Environmental Safety, 2024)
Manganese is essential trace elements, to participate in the body a variety of biochemical reactions, has important physiological functions, such as stimulate the immune cell proliferation, strengthen the cellular immunity, etc. However, excessive manganese exposure can cause damage to multiple systems of the body.The immune system is extremely vulnerable to external toxicants, however manganese research on the immune system are inadequate and biomarkers are lacking. Therefore, here we applied a manganese-exposed rat model to make preliminary observations on the immunotoxic effects of manganese. We found that manganese exposure inhibited humoral immune function in rats by decreasing peripheral blood IgG (ImmunoglobulinG, IgG), IgM (ImmunoglobulinM, IgM) and complement C3 levels; It also regulates rat cellular immune activity by influencing peripheral blood, spleen, and thymus T cell numbers and immune organ ICs (Immune Checkpoints, ICs) and cytokine expression. Furthermore, it was revealed that the impact of manganese exposure on the immune function of rats exhibited a correlation with both the dosage and duration of exposure. Notably, prolonged exposure to high doses of manganese had the most pronounced influence on rat immune function, primarily manifesting as immunosuppression.The above findings suggest that manganese exposure leads to impaired immune function and related changes in immune indicators, or may provide clues for the discovery of its biomarkers.